Strategi Mengatasi Tantangan Dalam Pelaksanaan Supervisi Pendidikan - Maritim, Ery (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This paper discusses educational supervision, the development of supervision, and the role of communication in the implementation of educational supervision. Educational supervision is a process of monitoring and coaching which aims to improve the quality of education in educational institutions. In its development, the concept of supervision underwent a transformation from an authoritarian approach to being inclusive and responsive to individual needs. Communication plays a key role in the implementation of effective educational supervision, facilitating reflection, building trusting relationships, and enabling constructive feedback between supervisor and supervisee. This paper also discusses the role of technology in educational supervision and the challenges faced in its implementation, as well as presenting strategies for overcoming these challenges.